2003
DOI: 10.1002/cncr.11423
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sentinel lymph node procedure using a combination of patent blue and radioisotope in women with cervical carcinoma

Abstract: The results of this study suggest that SN detection with a combination of radiocolloid and patent blue is feasible in patients with cervical carcinoma. The combination of laparoscopy and the SN procedure permitted minimally invasive management of early-stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 32 publications
2
30
0
7
Order By: Relevance
“…SN procedure. SN procedure was performed in accordance with previous studies using combined radiocolloid and colorimetric technique [7,9,12,13]. The position of each SN relative to the major pelvic vessels, and the count rate, were recorded.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…SN procedure. SN procedure was performed in accordance with previous studies using combined radiocolloid and colorimetric technique [7,9,12,13]. The position of each SN relative to the major pelvic vessels, and the count rate, were recorded.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…The sentinel lymph node (SN) procedure has emerged as a less aggressive alternative [7,9,10]. Moreover, serial sectioning and immunohistochemical analysis of SN can detect micrometastasis [7,9,10].…”
mentioning
confidence: 99%
“…In addition, the method of detection varied from study to study, with some investigators using only blue dye injection, 5,13,15 some using only radioisotope injection, 11,16 and some using a combination of these two methods. 10,12,14,17,18 Our preliminary study 5 indicated that SLN biopsy was reliable in predicting the status of the pelvic lymph nodes, with a negative predictive value of 100% for pelvic SLNs and NSLNs when classical pathologic evaluation techniques were used. Our experience with the assessment of this technique subsequently expanded, with more than 100 patients eventually being evaluated; the observed negative predictive value remained at 100%.…”
Section: Discussionmentioning
confidence: 94%
“…In a study of 50 patients with cervical cancer of FIGO stages I-IV by Malur et al, a combination of radioactively labeled albumin and blue dye yielded an SLN detection rate of 78 %. [11] Barranger et al emphasised in several publications that in cervical cancer, regional lymph node status is a major prognostic factor and a criterion for the use of adjuvant therapy [16]. They asserted that the SLN procedure based on blue dye and radiocolloid is suitable for evaluation of lymph node status.…”
Section: Discussionmentioning
confidence: 99%